New condition of harmonicity of functions of infinitely many variables (translation nonpositive case) - Feller, M. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A criterion of harmonicity of functions in a Hilbert space is given in the case of nonnegative second derivatives without using an assumption that they are mutually independent. This assumption is replaced by a weaker condition.